Impact of Benzodiazepine Use on Length of Stay and 30-Day ED Visits among Hospitalized Hematopoietic Stem Cell Transplant Recipients. Issue 12 (December 2022) - Niazi, Shehzad K.; Iqbal, Madiha; Spaulding, Aaron C.; Wood, Chanel; Manochakian, Rami; Paulus, Aneel; Ailawadhi, Sikander; Brennan, Emily; Kharfan Dabaja, Mohamed A.; Sher, Taimur
Abstract : Hematopoietic stem cell transplant (HSCT) is a potentially lifesaving and, for certain diseases, the only curative treatment. Patients undergoing HSCT are under stress and often experience anxiety and depression. Symptomatic treatment of distress and anxiety often involves benzodiazepines. This study describes how benzodiazepine use affects length of stay and 30-day emergency department visits in cancer patients hospitalized to receive an allogeneic or autologous HSCT. Abstract: Objectives: This study assesses the impact of benzodiazepine (BNZ) use on length of stay (LOS) and 30-day emergency department (ED) visits after hematopoietic stem cell transplant (HSCT). Methods: Adult patients (18 years and older) who underwent an allogeneic or an autologous HSCT from 2015 to 2018 at the study site were included. Five multivariable models were used for both allogeneic and autologous HSCT: BNZ-naïve status, diazepam equivalent daily dosage (DEDD; 0 vs any), DEDD (excluding 0), ED visits, and LOS. Results: BNZ-naïve autologous HSCT recipients were less likely to use any BNZs in the hospital (odds ratio [OR] 0.07, P < 0.001). If prescribed BNZs, then they used a lesser amount (incidence rate ratio 0.39, P < 0.001). BNZ-naïve autologous HSCT recipients were less likely to experience a 30-day ED visit (OR 0.17, P = 0.009). BNZ-naïve allogeneic HSCT recipients were also less likely to use any BNZ than previous users (OR 0.11, P = 0.014). Patient characteristics influenced BNZ naïvety, DEDD usage, LOS for autologous patients, and BNZ naïvety and DEDD for allogeneic patients. Conclusions: BNZ use resulted in increased 30-day ED visits after autologous HSCT. BNZ-naïve recipients were less likely to use BNZs during hospital stays; if they required BNZs, then it was in lower dosages.